Development plan of athletes, swimmers, and gymnasts in Korea - Nam, Y. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
The level of elite sports in Korea has reached the world level. Overall ranking of Korea since the 2004 Athens Olympics is steadily in world`s top 10 holding (Korean Olympic Committee, www.sports.or.kr). Although the basic events have many medals, Korean government gives no special support to these events since it is very difficult to have medals and the player base is not in a good condition. The purpose of this study is to suggest how to expand the player base of the basic events in Korea. For this purpose, literature survey and field research, including in-depth interviews, were conducted. We analyzed the importance of the basic events, logical development of policy support, the development status of the player base by sports associations and expansion status of underlying basic events in advanced countries. The first survey was performed on 31 responses consisted of athletic directors of school sports on the basis of population of 48 elementary, middle, and high school. The second survey was performed on 7 representative populations of school physical education. The third survey was conducted by Korea Association of Athletics Federations, Korea Swimming Federation, Korea Gymnastic Association. All surveys were conducted via e-mail. The site survey was conducted on development and operating status by sports organizations. Study area was in Seoul, Gyeonggi, and Daejeon. Every two school was selected for the site survey. In-depth interviews were conducted on school sports club leaders and instructors, school athletic leaders of athletics, swimming, and gymnastics. As the result, although school sports club enrollment was significantly increased, the enrollment ratio of the school sports clubs was found to be quite inflated numerically due to the lack of physical education space, poor physical facilities, and the lack of leadership. Unclear future of players and lack of competition in physical education-centered schools caused unactivation of the basic events. To expand the player base of the basic events, first of all, business promotion should be performed through pre-school life sports / school physical education. As the business of Korea Council of Sport for All related to the basic events, classroom, group and competition projects should be included for the extension of the player base. In particular, the government needs to promote the expansion business for the player base of the basic events separately or to promote youth physical activity business. The business on Sports Council for Gifted, which is being carried out by Korean Olympic Committee and Korea Foundation for the Need Generation Sports Toward, should be promoted mainly by Korean Olympic Committee, and performed by dividing it into two parts: pre-school from the age of seven to fourth grade of elementary school and from fifth grade of elementary school to first grade of middle school. While the basic events are considered to be difficult and uncertain, these events must be a very valuable asset to the player and an extremely useful for pragmatic sociability.